Epipelic Algae Assemblage and Nutrient Status as Indicators of Pollution in Alice Creek, Rivers State, Nigeria - O.A. Bubu-Davies; A.L.Esaenwi; A. Bob-Manuel (International Journal of Marine Life, 2025)
Background and Objective: Alice creek is a tributary of the Sombreiro River, Akuku-Toru Local Government Area, Rivers State, Nigeria, receiving various anthropogenic wastes. The study investigated the species composition, diversity, abundance, and distribution of epipelic algae, and the nutrient status of Alice creek, a tributary of Sombreiro river, Rivers State, Nigeria. Materials and Methods: Epipelic and nutrients samples were collected monthly between February and May 2020 from three (3) stations [Ogonikiri (Station 1), Onubio-Okolobio waterside (Station 2), and College Site-bridge (Station 3)] established along the watercourse of the creek following standard method. Epipelic algae were identified microscopically. Phosphate and ammonia were analyzed following scientific procedures. Data analyses were subjected to analysis of variance and descriptive statistics. Results: The study recorded a total of six (6) families, twenty-six (26) genera, thirty-one (31) species, and fifty-two (52) individuals of epipelic algae were encountered in the study. The percentage composition of epipelic algae observed was Bacillariophyceae (30.77%), Chlorophyceae (21.15%), Euglenophyceae (17.31%), Dinophyceae (15.38%), Xanthophyceae (13.46%) and Cyanophyceae (1.92%). The most dominant species were Glenodinium 2 elphatiewskyi (909 no./ml), Trachelomonas lacustris (909 no./ml), and Tribonema viride (909 no./ml). The analyzed nutrients were phosphate (0.34±0.08 mg/L) and ammonia (5.83±0.98 mg/L), higher than 0.1 mg/L and 0.01-2.00 mg/L of USEPA standard, respectively. The increased amount of nutrients favoured indicator species such as Cyclotella comta, C. meneghiniana, C. operculate (Bacillariophyta), Scenedesmus acuminatus (Chlorophyta), and Euglena pisciformis (Euglenophyta). Conclusion: The presence of dominant species (Glenodinium elphatiewskyi (Dinophyta), Trachelomonas lacustris (Euglenophyta) and Tribonema viride (Xanthophyta) and pollution-indicator species [Cyclotella comta, C. meneghiniana, and C. operculate (Bacillariophyta), Scenedesmus acuminatus (Chlorophyta), and Euglena pisciformis (Euglenophyta)], as well as high ammonia and phosphate, indicate stress and organic pollution in Alice Creek.
Keywords: Epipelic algae; Nigeria; Rivers State; abundance; species composition; species diversity